2014
DOI: 10.7314/apjcp.2014.15.9.3987
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Induces Apoptosis in SGC-7901 Gastric Adenocarcinoma Cells via Regulation of Mitochondrial Signaling Pathways

Abstract: Curcumin, a polyphenol compound derived from the rhizome of the plant Curcuma longa L. has been verified as an anticancer compound against several types of cancer. However, understanding of the molecular mechanisms by which it induces apoptosis is limited. In this study, the anticancer efficacy of curcumin was investigated in human gastric adenocarcinoma SGC-7901 cells. The results demonstrated that curcumin induced morphological changes and decreased cell viability. Apoptosis triggered by curcumin was visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 35 publications
3
27
0
2
Order By: Relevance
“…The mitochondria-mediated apoptotic pathway is characterized by loss of MMP and release of cytochrome c from mitochondria into the cytoplasm (28). In the present study, the mitochondrial-specific cationic dye, JC-1, was used to confirm the loss of MMP upon exposure to curcumin, and an immunofluorescence assay showed cytochrome c translocation, occurring in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 82%
“…The mitochondria-mediated apoptotic pathway is characterized by loss of MMP and release of cytochrome c from mitochondria into the cytoplasm (28). In the present study, the mitochondrial-specific cationic dye, JC-1, was used to confirm the loss of MMP upon exposure to curcumin, and an immunofluorescence assay showed cytochrome c translocation, occurring in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 82%
“…Apoptosis can be triggered by various stimuli, including death receptor-mediated signaling and intracellular stress (Banjerdpongchai and Kongtawelert, 2011). It is well known that Cyt C triggers the activation of caspase cascade in the intrinsic apoptotic pathway if released from mitochondrial membrane gap into cytoplasm (Garrido et al, 2006;Xue et al, 2014). Cyt C is so called the Achilles' heel in apoptosis, for its promotion in the process of apoptosis irreversibly (Kulikov et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry showed that the cells treated with AHL have effectively arrested in G2/M phase. Abnormality in cell cycle regulation implies the following apoptosis event, which leads to the proliferation inhibition of HepG-2 cells (Xue et al, 2014).…”
Section: Discussionmentioning
confidence: 99%